Efecto de tres dosis de fertilización foliar en las plantas de Swietenia macrophylla “caoba” en plantación. Puerto Almendra, Loreto, Perú - 2021 - Palomino Inuma, Tatiana Fabiola (2022)
The thesis was carried out in a plantation of CIEFOR Puerto Almendra FCF - UNAP, located in San Juan Bautista, Maynas, Loreto, Peru. The objective of the study was to determine the effect of three doses of foliar fertilization on the growth, survival and quality of Swietenia macrophylla "caoba" plants in a CIEFOR plantation - Puerto Almendra, Loreto, Peru - 2021. Strips “B”, “F”, “I” were used from plot 1; “C”, “E”, “J” from plot 2; “C”, “D”, “H”, “K” of plot 5 and “B” from plot 6 of the plantation. The results indicate that the Swietenia macrophylla “caoba” plants with foliar fertilization of 60 ml of concentrate / 200 ml of water (treatment 3) were the ones that presented the best increase in total height; in diameter, it was treatment 2 (40 ml of concentrate / 200 ml of water) that presented the greatest increase; it was also found in the study between 70% and 75% survival of the plants at the end of the trial; The quality of the plants of the species Swietenia macrophylla "caoba" at the end of the trial was REGULAR for all treatments (doses) and in general. According to the statistical analysis, there is no statistical difference between the doses applied in the study for the diameter, total height and survival of the plants of the species studied with 95% confidence.